ANTIBACTERIAL ACTIVITY OF LOBELIA NICOTIANIFOLIA AGAINST VARIOUS BACTERIAL STRAINS: Life Sciences-Bio Chemistry - S. KUNCHARI KALAIMATHI; G. MUTHU; K. MANJULA (International Journal of Life Science and Pharma Research, 2022)
Indian tribal folks had used plant based natural products as curative agents for various illnesses, which is evidenced from Rig-Veda dated back 1500 B.C. In this study, powdered plant material, leaves of Lobelia nicotianifolia sequentially extracted using methanol, ethyl acetate, acetone, chloroform, petroleum ether and water. Then the extracts were concentrated to dryness by evaporating the solvent at 40ºC. In vitro antibacterial activity of these extracts was studied by agar well diffusion method against gram positive Staphylococcus aureus and gram negative Pseudomonas aeruginosa, Salmonella typhi as well as Escherichia coli. Ciproflaxin, Cephotoxime and Amoxycillin antibiotic discs were used as standard. This study demonstrated that the methanol extract has higher antibacterial activity against clinical isolated bacterial pathogens than other extracts. All these extracts were able to inhibit the growth of Staphylococcus aureus, Escherichia coli, Salmonella typhi and Pseudomonas aeruginosa except peteroleum ether extract and ethyl acetate extract. This present study concluded that Lobelia nicotianifolia has strong antibacterial activity against clinical micro-organism. However, further studies should be needed for the isolation and characterization of these active compounds from Lobelia nicotianifolia.